Electrocardiographic changes after TAVR and their clinical impact according to new ESC Pacing Guidelines. (3rd October 2022) - Lueg, J; Morell, L; Juri, B; Janiszewski, A; Hajduczenia, M; Hennig, P; Niehues, S; Dreger, H; Leistner, D; Landmesser, U; Stangl, K; Tscholl, V
Abstract:  : Conduction disturbances after transcatheter aortic valve replacement (TAVR) remain one of the most frequent complications. The aim of this study was to analyze ECG changes after TAVR using contemporary valves and to detect risk factors for the need of further clinical evaluation according to new ESC pacing guidelines to evaluate pacemaker implantation. In this retrospective analysis we included 850 patients (mean age 80±9 years, 51% female), who underwent TAVR in our institution from January 2019 until December 2020. A mean follow-up of 8.9±8.4 months and 217 (25.5%) patients was performed. 55% of the implanted valves were self-expandable, 45% balloon-expandable. After TAVR, 77 (9.1%) patients developed new LBBB and QRS >150ms, 26 (3.1%) new PR-time >240ms. Prolongation of PR-time and prolongation of QRS duration >20ms were seen in 20 (2.4%) and 90 (10.6%) patients with preexisting conduction disturbances. 152 (17.9%) patients needed pacemaker implantation post TAVR. Developing a PR-prolongation of >20ms was associated with calcification of the annulus (OR 1.2 CI 95% 1.004–1.4; p=0.04). New LBBB (OR 0.45; CI 95% 0.25–0.79; p=0.006) and pacemaker implantation (OR 0.4; CI 95% 0.2–0.8; p=0.009) were correlated with the implantation of a self-expandable valve. Coronary heart disease (OR 3, CI 95% 1.07–8.2; p=0.04) and peripheral arterial disease (OR 2.6 CI 95% 1.18–5.6; p=0.02) were associated with prolongation of QRS >20ms. New LBBB with QRS >150ms was seen more often after post-dilatation (OR 1.03, CI 95% 1.01–1.05; p=0.05). Pre-existing AV block I° (OR 2.8, CI 95% 1.4–5.6; p<0.001), pre-existing RBBB (OR 20.5, CI 95% 7.5–56; p<0.001), nicotine abuse (OR 2, CI 95% 1.05–3.8; p=0.04), prosthesis oversizing (OR 1.06, CI 95% 1.006–1.11; p=0.03) and implantation depth (OR 1.13, CI 95% 1.006–1.26; p=0.04) were independent risk factors for pacemaker implantation. During the follow-up 161 patients (18.9%) were hospitalized in 270 inpatient stays [cardiac decompensation (n=36, 13%), pacemaker implantation (n=9, 3.3%), acute coronary syndrome (n=12, 4.4%)]. 8 patients (80%) received a pacemaker implantation because of AV Block III° and 1 (10%) patient because of sick-sinus-syndrome (SSS). Analyzing the post TAVR ECG 5 (50%) had a new LBBB (3 (30%) with QRS >150ms) and 4 (40%) patients showed LBBB together with AV Block I°. According to new guidelines 213 (25.1%) patients would have needed further clinical evaluation (EP study or ECG monitoring) after TAVR. AV-conduction abnormalities were associated with annulus calcification. Self-expandable valves were associated with new LBBB and pacemaker implantation. There seems to be a correlation between arteriosclerotic diseases and QRS width post TAVR. Pre-existing RBBB, AV block I°, implantation depth and prosthesis oversizing are important risk factors for pacemaker implantation post TAVR. New LBBB after TAVR is associated with a higher risk for pacemaker implantation in the long-term analysis. Funding Acknowledgement: Type of funding sources: None.